Effect of static and dynamic core exercises on kicking impact, kicking speed and balance in adolescent taekwondo athletes (Revista de Artes Marciales Asiáticas, 2025)
The aim of this study was to determine the effects of static and dynamic core exercises on kicking impact (KI), kicking speed, and balance in adolescent taekwondo athletes. Thirty-three adolescent taekwondo athletes were randomly divided into three groups: static core (SC, n=11), dynamic core (DC, n=11), and control group (CON, n=11). SC and DC group performed core exercise programs in addition to taekwondo training three days a week for eight weeks. KI was determined with the electronic body protector. The frequency speed of kick test (FSKT10s) was applied to kicking speed. The flamingo balance test for static balance (SB) and lower and upper quarter Y-balance test (YBT-LQ & YBT-UQ) for dynamic balance were used. KI increased significantly only on the non-dominant side in the DC group (p=.001). A significant improvement in FSKT10s score was detected in the SC group (dominant, p